Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


P(x) = (x-4) (x+3) (x-1)
= (x²+3x-4x-12) (x-1)
= (x²-x-12) (x-1)
= x³-x-x²+x-12x+12
= x³-x²-12x+12.......... It is the required polynomial equation.

0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts